Pengaruh Penghindaran Pajak, Net Working Capital, Growth Opportunity Dan Cash Convertion Cycle Terhadap Cash Holding - Free Antonius simanjuntak; Farina Jessen Yap (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Determination of optimal cash holdings is necessary because cash is an element of working capital that is most needed by a company to fulfill the company's daily operations, therefore this study aims to determine and analyze the effect of tax avoidance, net working capital, growth opportunity and cash. convertion cycle to cash holding.This type of research is a quantitative study using observation data collection techniques, interviews and documentation. The number of population and samples in this study were 48 data. The data analysis technique used is multiple linear regression analysis, classical assumption test and hypothesis testing.The results of this study indicate that tax avoidance, net working capital,growth opportunity and cash conversion cycle have a significant effect on cash holding. The partial test results show that tax avoidance has no effect on cash holding, net working capital and cash conversion cycle has a positive effect on cash holding, while growth opportunity has a negative effect on cash holding. The conclusion of this research is tax avoidance, net working capital, growth opportunity and cash conversion cycle have a significant effect on cash holding 36.6% and the remaining 63.4% is explained by other independent variables not examined in this study such as leverage and cash flow.